Epizootiology and associated risk factors of tick fauna infecting domestic livestock population in district Faisalabad, Punjab, Pakistan - Maqbool, M; Sajid, MS; Iqbal, Z; Saqib, M (Journal of the Hellenic Veterinary Medical Society, 2022)
The current study was aimed to corelates the association of different risk factors with tick infestation rate in livestock (cattle, buffalo, sheep, goat) population of district Faisalabad. Ticks were collected through the standard collection protocols, were identified under stereomicroscope. Overall, 54%, 50%, 50% and 49 % tick infestation rate reported from livestock species (cattle, buffalo, sheep, goat) and higher prevalence was observed in tehsil Tandlianwala (72%, 65%, 70% and 57%). Among intrinsic factors (age and sex) higher prevalence was reported in young (7-12 months) and female animals. Significant association (P<0.05) was observed with season and tick prevalence and higher prevalence was reported in summer season. Statistically significant association (P<0.05) was observed among extrinsic factors including feeding system, (higher infestation was reported in grazing animals), housing system (higher rate was recorded in free-housed animals), type of farming (higher rate in free-ranged animals), farm structure (higher infestation rate among animals kept on uncemented floor) and hygienic measures (higher prevalence in poorly hygiene animals). Most prevalent tick species were H. anatolicum, (85%), H. marginatum (1.5%), H. turncatum (1.02%) and R. microplus (12%). These findings will be helpful in devising services for tick infestation control in selected area and other regions having similar husbandry system.